Biochemical and Structural Characterization of a Novel Bacterial Tannase From Lachnospiraceae bacterium in Ruminant Gastrointestinal Tract - Guan, Lijun; Wang, Kunlun; Gao, Yang; Li, Jialei; Yan, Song; Ji, Nina; Ren, Chuanying; Wang, Jiayou; Zhou, Ye; Li, Bo; Lu, Shuwen (Frontiers in Bioengineering and Biotechnology, 2021)
Tannases are a family of esterases that catalyze the hydrolysis of ester and depside bonds present in hydrolyzable tannins to release gallic acid. Here, a novel tannase from Lachnospiraceae bacterium (TanALb) was characterized. The recombinant TanALb exhibited maximal activity at pH 7.0 and 50°C, and it maintained more than 70% relative activity from 30°C to 55°C. The activity of TanALb was enhanced by Mg2+ and Ca2+, and was dramatically reduced by Cu2+ and Mn2+. TanALb is capable of degrading esters of phenolic acids with long-chain alcohols, such as lauryl gallate as well as tannic acid. The Km value and catalytic efficiency (kcat /Km) of TanALb toward five substrates showed that tannic acid (TA) was the favorite substrate. Homology modeling and structural analysis indicated that TanALb contains an insertion loop (residues 341–450). Based on the moleculer docking and molecular dynamics (MD) simulation, this loop was observed as a flap-like lid to interact with bulk substrates such as tannic acid. TanALb is a novel bacterial tannase, and the characteristics of this enzyme make it potentially interesting for industrial use.